Improvement of Cancer Immunotherapy by Combining Molecular Targeted Therapy - Kawakami, Yutaka; Yaguchi, Tomonori; Sumimoto, Hidetoshi; Kudo-Saito, Chie; Iwata-Kajihara, Tomoko; Nakamura, Shoko; Tsujikawa, Takahiro; Park, Jeong H.; Popivanova, Boryana K.; Miyazaki, Junichiro; Kawamura, Naoshi (Frontiers in Oncology, 2013)
In human cancer cells, a constitutive activation of MAPK, STAT3, β-catenin, and various other signaling pathways triggers multiple immunosuppressive cascades. These cascades result in the production of immunosuppressive molecules (e.g. TGF-β, IL-10, IL-6, VEGF, and CCL2) and induction of immunosuppressive immune cells (e.g. regulatory T cells, tolerogenic dendritic cells, and myeloid derived suppressor cells). Consequently, immunosuppressive conditions are formed in tumor-associated microenvironments, including the tumor and sentinel lymph nodes. Some of these cancer-derived cytokines and chemokines impair immune cells and render them immunosuppressive via the activation of signaling molecules, such as STAT3, in the immune cells. Thus, administration of signal inhibitors may inhibit the multiple immunosuppressive cascades by acting simultaneously on both cancer and immune cells at the key regulatory points in the cancer-immune network. Since common signaling pathways are involved in manifestation of several hallmarks of cancer, including cancer cell proliferation/survival, invasion/metastasis, and immunosuppression, targeting these shared signaling pathways in combination with immunotherapy may be a promising strategy for cancer treatment.